IMPROVING THE EFFICIENCY OF THE TECHNOLOGY OF CLEANING SEED COTTON FROM LARGE IMPURITIES (Journal of Science-Innovative Research in Uzbekistan, 2024)
One of the main economic efficiency of the new UXK machine for cleaning seeded cotton from small and large impurities, which is described in this article, is the reduction of electricity consumption and the level of damage to seeded cotton. Mainly, instead of the mesh surface on the lower part of the first pile drum of the UXK working part, the columns moving through the belt transmission were used, that is, the column under the pile drum also moves together